Fuzzy based energy management algorithm for hybrid train systems / Ahmad Mirabadi and Najafi M. - Mirabadi, Ahmad; Najafi, M. (UiTM Press, 2010)
Energy management is one of the key issues in designing different types of hybrid vehicles, including cars, buses and trains. In this paper a hybrid train is studied in three modes of operation, using three different power sources. In order to keep the energy consumption at an optimum level, it is necessary to consider the characteristics of all the system's elements and also their optimum point of service. A fuzzy logic based energy management system has been designed and implemented. The underlying subject of the fuzzy based energy management system is to optimize the efficiency of internal combustion engine, ICE, considering the other power sources as flywheel and battery. Simulation results have been used to evaluate the performance of the fuzzy logic energy management system.